IMPACT OF CHILD SEXUAL ABUSE ON CHILDREN WITHIN INTERNALLY DISPLACED PERSONS HOST COMMUNITIES: A MIXED-METHODS STUDY IN MAIDUGURI METROPOLIS, NIGERIA - Mu’azu, Idris; Umar Dahiru, Aishatu; Isa Geidam, Aisa (African Journal of Social and Behavioural Sciences, 2026)
Child sexual abuse (CSA) has severe and lasting impacts on victims, particularly among vulnerable populations such as children in internally displaced persons (IDPs) communities. This study examined the multidimensional impacts of CSA on children within IDP host communities in Maiduguri Metropolis, Borno State, Nigeria. A mixed-methods design combining quantitative surveys (N=331) and qualitative Key Informant Interviews (N=15) was employed. Structured questionnaires assessed psychological, health, and social impacts of CSA. Descriptive statistics and correlational analyses were used to identify associated impact factors, while thematic analysis explored qualitative narratives. The study identified significant psychological impacts including depression and sleep disturbance (36.6%), shame and stigma (26.3%), disappointment and frustration (22.7%), fear and anxiety (10.0%), and anger (4.5%). Health impacts included HIV/STD (29.3%), emotional disturbance (27.8%), infertility (22.7%), and mental instability (20.2%). Social impacts comprised stigmatization (36.6%), low self-esteem (26.3%), alcohol consumption (22.7%), drug consumption (10.0%), and interpersonal relationship difficulties (4.5%). A descriptive correlational analysis revealed that most identified consequences showed significant associations with overall CSA impact severity (p < 0.05), though depression approached but did not reach statistical significance (p = 0.076). The model accounted for 67% of the variance (R² = 0.67). Child sexual abuse has profound and multifaceted impacts on children in IDP host communities, affecting psychological well-being, physical health, and social functioning. These findings underscore the urgent need for comprehensive, survivor-centred interventions addressing the complex sequelae of CSA in displacement contexts.